Perancangan Komunikasi Visual Web Games Interaktif â€œGooclean.Comâ€ Guna Menanamkan Budaya Anti Korupsi Sejak Dini - Darmawan, Andreas James; Bonafix, Nunnun (Humaniora, 2011)
Along with the increasing number of corruption, the role of visual communication is also increasingly necessary. Its role is as a maker of communications media that attract, encourage, and interactive. So the anti-corruption culture that wants implanted were well received and is embedded in the consciousness of the receiver behave. Article clarifies visual communication "Gooclean" intended for children and packaged in attractive web-based games to play while learning interests of children. The research method discussed is literature study for having the basic theory, comparative study observation with other anti corruption wesites, also interview with project PIC. The scope of Gooclean interactive web games is presented interestingly to increase children?s interest towards the presented material. This is presented by interesting illustration, challenging games, and visual concept that children will understand easily.